INVESTIGATION OF CORRELATIONS OF GENERATED NUCLEAR ACTIVE PARTICLES IN p p - EVENTS ENRICHED BY ANNIHILATION AT MOMENTA 22.4 GeV/c AND 32 GeV/c - M. Izbasarov; N.S. Pokrovsky; V.V. Samoilov; T. Temiraliev; R.A. Tursunov; B.O. Zhautykov (Academic Scientific Journal of Computer Science, 2019)
Extraction of p p - events, enriched by annihilation, allowed to carry out the analysis of multiparticle correlations for the generated particles. The correlation function R (G) k is characterizing the ratio of experimental differential distribution of quasi-rapidity intervals to differential background distribution The analysis of K R dependence on G was carried out on events enriched by annihilation and non – annihilation p p - interactions at momenta 22,4 GeV /c and 32 GeV / c, and also inelastic pp - collisions at momentum 69 GeV/c. In interactions with “annihilation” more weak correlation of charged particles is observed, than in nonannihilation p p - interactions. In proton – proton and non - annihilation antiproton – proton collisions similarity of correlation functions is observed.